Comprehensive analysis of organophosphorus flame retardant-induced mitochondrial abnormalities: Potential role in lipid accumulation. (1st April 2021) - Le, Yifei; Shen, Haiping; Yang, Zhen; Lu, Dezhao; Wang, Cui
Abstract: Organophosphorus flame retardants (OPFRs), a group of new emerging endocrine disruption chemicals, have been reported to cause metabolic disturbance. Currently, mitochondrial abnormality is a new paradigm for evaluating chemical-mediated metabolic disruption. However, a comprehensive correlation between these two aspects of OPFR remains elusive. In the work reported here, 3 markers for morphological abnormality, and 7 markers of mitochondrial dysfunction were detected after treatment with two aryl-OPFRs (TCP and TPhP) and three chlorinated-OPFRs (TDCPP, TCPP, and TCEP) on hepatocyte. The two aryl-OPFRs and TDCPP can cause intracellular lipid accumulation at non-cytotoxic concentrations (<10 μM), while the other two chlorinated-OPFRs only caused lipid deposition at 10 μM. Furthermore, at the tested concentrations, all of them reduced mitochondrial (mito)-network numbers, enlarged mito-area/cells, and skewed mitoATP/glycoATP. Excluding TCEP, the other four chemicals induced mito-ROS and depleted mitochondrial membrane potential (MMP). Notably, only TCP, TPhP and TDCPP impeded mitoATP generation rate and mito-respiratory rate. Based on potency estimates, the capacity for lipid accumulation was significantly correlated with mito-network numbers (R 2 = 0.6481, p < 0.01), mitoATP/glycoATP (R 2 = 0.5197, p < 0.01), mitoROS (R 2 = 0.7197, p < 0.01), and MMP (R 2 = 0.7715, p < 0.01). Remarkably, the mito-respiratory rate (R 2 = 0.8753, p < 0.01) exhibited the highest correlation. Thus, the more potent lipid inducers TPhP, TCP and TDCPP could be identified. The results of this study demonstrate that aryl-OPFRs are more potent in metabolic disruption than other esters examined. Metabolic disruption should be examined further for chemicals that have the capacity to counteract the aforementioned functions of mitochondrial. Graphical abstract: Image 1 Highlights: Aryl-OPFRs (TPhP, TCP) induced seven biomarkers of mitochondrial abnormalities. TDCPP was the most toxic to mitochondrial among the three chlorinated-OPFRs. TPhP and TCP induced more lipid than three chlorinated-OPFRs. Five biomarkers of mitochondrial dysfunction related to OPFRs-induced lipid. Potent of impairment of mito-respiratory rate was highly related to lipid accumulation.